2015
DOI: 10.1080/08989621.2014.955607
|View full text |Cite
|
Sign up to set email alerts
|

Researcher Perceptions of Ethical Guidelines and Codes of Conduct

Abstract: Ethical codes of conduct exist in almost every profession. Field-specific codes of conduct have been around for decades, each articulating specific ethical and professional guidelines. However, there has been little empirical research on researchers’ perceptions of these codes of conduct. In the present study, we interviewed faculty members in six research disciplines and identified five themes bearing on the circumstances under which they use ethical guidelines and the underlying reasons for not adhering to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 29 publications
1
25
0
1
Order By: Relevance
“…It is essentially required to follow good scientific practice guidelines and procedure in scientific research (51). Ethical guidelines have been applied to the overall research process to maintain high ethical standards (51,52). The review was undertaken according to responsible ethical conduct considering transparency and rigour of the research process.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…It is essentially required to follow good scientific practice guidelines and procedure in scientific research (51). Ethical guidelines have been applied to the overall research process to maintain high ethical standards (51,52). The review was undertaken according to responsible ethical conduct considering transparency and rigour of the research process.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…Research questions of this type tend to be variations of 'how many is' , 'what is' and 'why is' . The second trend is examining researchers responses on and attitudes towards ethical issues and concepts (Giorgini et al, 2015;Löfström, 2012;Schuurbiers et al, 2009). There is also a genre of publications on whether a certain area or field should create a code of its own (Mwaka, 2017;Rossouw, Zyl, & Pope, 2014), as well as what could be called accompanying literature to published CoCs (Drenth, 2006;Karjalainen, Launis, Pelkonen, & Pietarinen, 2002;Löppönen et al, 1991;Steneck, Anderson, Kleinert, & Mayer, 2015).…”
Section: Relevant Previous Researchmentioning
confidence: 99%
“…Ford and Richardson’s (1994) review of literature on ethical decision making showed inconsistent findings regarding the influence of codes of conduct on ethical behavior. This may be explained by the fact that specific organizations and institutions tend to vary widely with regard to the extent to which codes are enforced and the degree to which codes of conduct are considered a part of the organizational culture (Giorgini, Mecca, Gibson, Medeiros, Mumford, Connelly, & Devenport, in press). Additionally, within a field, there is a community of which all members are a part, with the assumption being that people are social beings driven to act in accordance with social norms.…”
Section: Field-specific Guidelinesmentioning
confidence: 99%